Once again about determination of saving of energy for traction due to partial cut–off of traction engines of electric rolling stock - Getman, G. K.; Vasiliev, V. Ye. (Science and Transport Progress, 2013)
Purpose. In general the well known methods for determination of energy saving due to the partial traction engines cut-off based on their comparison to efficiency coefficient or to the power of energy losses do not allow objective estimation of efficiency of these measures and in a number of cases result in erroneous results and errors. The search for new more advanced methods for determination of energy saving at the partial cut-off of the traction engines is needed. Methodology. The method of calculation determination of energy saving when partial cutting-off of the traction engines is offered. It is based on the use of rationality coefficient as the loading mode of the electric power consumption for the measuring instrument of transportation activity. Findings. Using the given mathematical expressions it is possible to determine the energy saving in both the relative and absolute values and set the terms (motion speed and route gradient), under which the energy saving will take place. Originality. The method of the task solving, which is based on the evaluation of energy consumption differences for the compared variants (not on the comparison of efficiency coefficient or differences of power of energy losses) is offered. Practical value. The given methodology allows obtaining more exact conclusions in relation to the electric power consumption, as the comparison of energy losses power or the efficiency coefficient does not determine precisely the electric power consumption for traction. Therefore the conclusions based on the comparison of power of energy losses or efficiency coefficient can appear inexact.